2019
DOI: 10.1080/0284186x.2019.1633016
|View full text |Cite
|
Sign up to set email alerts
|

LINAC based stereotactic radiosurgery for multiple brain metastases: guidance for clinical implementation

Abstract: Introduction: Stereotactic radiosurgery (SRS) is a promising treatment option for patients with multiple brain metastases (BM). Recent technical advances have made LINAC based SRS a patient friendly technique, allowing for accurate patient positioning and a short treatment time. Since SRS is increasingly being used for patients with multiple BM, it remains essential that SRS be performed with the highest achievable quality in order to prevent unnecessary complications such as radionecrosis. The purpose of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 52 publications
(58 reference statements)
0
61
0
Order By: Relevance
“…In contrast, for a limited number of metastases (1-4), stereotactic radiosurgery is the option of first choice in most cases. Recent technological advances have made linac-based frameless SRS a more patient friendly treatment option, allowing for accurate patient positioning and shorter treatment times [41][42][43][44][45]. Since SRS is increasingly used in patients with multiple BM, it is important that SRS is performed with the highest quality achievable to avoid complications such as radionecrosis.…”
Section: Intracranial Tumors: Wbrt and Srsmentioning
confidence: 99%
“…In contrast, for a limited number of metastases (1-4), stereotactic radiosurgery is the option of first choice in most cases. Recent technological advances have made linac-based frameless SRS a more patient friendly treatment option, allowing for accurate patient positioning and shorter treatment times [41][42][43][44][45]. Since SRS is increasingly used in patients with multiple BM, it is important that SRS is performed with the highest quality achievable to avoid complications such as radionecrosis.…”
Section: Intracranial Tumors: Wbrt and Srsmentioning
confidence: 99%
“…For example, EGFR/ALK TKIs had significant intracranial activity and could achieve longer intracranial progression free survival, higher overall response rate than chemotherapy or radiotherapy, which have been proved in many retrospective and prospective studies 18–22 . And some studies have confirmed that stereotactic radiotherapy (SRS) was a well‐tolerated safe option for patients with four or more BM 23–25 . Besides, we also found that most patients with BM from NSCLC present with 0–1 ECM site and these patients showed superior survival.…”
Section: Discussionmentioning
confidence: 65%
“…Other strategies to maximize treatment efficiency include distortion correction of MR imaging and the use of flattening filter photon beams that ensure a lower peripheral dose and shorten the treatment time. 27 …”
Section: Discussionmentioning
confidence: 99%